Pelatihan Pembuatan Modul Ajar Berbasis Artificial Intelligence (AI) untuk Guru-Guru SMPN 3 Sungai Kakap - Manisa, Tesa; Trisianawati, Eka; Sari, Mustika; Nawawi, Nawawi; Herditiya, Herditiya; Nurmayanti, Novi (Penerbit Goodwood, 2024)
Purpose: The purpose of this Community Service is to increase knowledge about making AI-based teaching modules and to produce complete teaching modules that are in accordance with the demands of the Merdeka curriculum. Research methodology: Community Service activities consist of preparation, implementation, and evaluation stages. The implementation of Community Service is carried out using lecture methods, interactive discussions, direct practice, assignments, and collection of teaching modules to increase teacher abilities and creativity. Data were collected using a Likert scale questionnaire with the criteria of activities running very well to not well. Results: The implementation of Community Service is carried out using lecture methods, interactive discussions, direct practice, assignments, and collection of teaching modules to increase teacher skills and creativity. The products produced by teachers are complete and intact teaching modules that can be collected on the Google Drive link. This link can be accessed by the principal, teachers, and study programs as facilitators in mentoring sessions during assignments. Proof that teachers have completed the training is in the form of a 32 JP certificate that can be uploaded to the PMM account to add teaching points. Limitation: This training may be limited by the infrastructure and technology access conditions at SMPN 3 Sungai Kakap. For example, limited hardware such as computers, unstable internet, or limited access to more sophisticated AI devices can limit the effectiveness of the training. Contribution: The Community Service Team would like to thank LPPM IKIP PGRI Pontianak as the funder, as well as the principal, teachers, and staff of SMPN 3 Sungai Kakap for their assistance.